An in silico rat liver atlas. Issue 10 (26th July 2020) - Ho, Harvey; Dahmen, Uta; Hunter, Peter
Abstract: Numerous hepatic function, disease and pharmacological experiments are performed on rat livers. Many of these experiments rely on an accurate understanding of the rat liver anatomy. In this short paper, we present an in silico rat liver atlas which is constructed from the micro-CT images of explanted rat livers. The atlas consists of the parametric mesh for four liver lobes and a paracaval portion. 1D and 3D cubic Hermite mesh are used to represent the rat liver vessels and lobes, respectively. We discuss potential applications that can be performed from the in silico atlas.